Facial, verbal, and symbolic stimuli differently affect the right hemisphere preponderance of stimulus‐preceding negativity. (22nd May 2014) - Ohgami, Yoshimi; Kotani, Yasunori; Arai, Jun‐Ichirou; Kiryu, Shigeru; Inoue, Yusuke
Abstract The present study investigated whether the right hemisphere preponderance of stimulus‐preceding negativity (SPN) was affected by different categories of visual feedback stimulus. A time estimation task was performed with facial, verbal, symbolic, and no‐feedback conditions. A principal component analysis identified an early component of SPN in addition to a late component that was morphologically similar to the original SPN. Motivational scores in the verbal and facial conditions were higher than that in the symbolic condition. Significant right hemisphere preponderance of the late SPN was observed in the symbolic condition but not in the verbal condition, whereas right hemisphere preponderance of the early SPN was observed in the facial condition. The right hemisphere preponderance was influenced by the category of visual feedback stimulus through stimulus‐related activation and the effect of the motivational level.